Enhancing the effectiveness of entrepreneurship education: the role of entrepreneurial lecturers. Issue 7 (28th March 2019) - Otache, Innocent
Abstract : Purpose: Despite the inclusion of entrepreneurship education (EE) in the curricula of tertiary education institutions in Nigeria, graduate unemployment is still an issue of serious concern. This calls into question the effectiveness of EE in influencing students' entrepreneurial intentions (EIs) and behaviours. Perhaps, the issue is with the EE lecturers. The questions, which should be answered include: are the lecturers who teach EE entrepreneurially inclined? Can lecturers who are not entrepreneurially inclined teach students to become entrepreneurs? The purpose of this paper, therefore, is to empirically explore the role of entrepreneurial lecturers in the relationship between EE and students' EIs. Design/methodology/approach: This study adopted a quantitative approach. Thus, a self-reported questionnaire was administered to a randomly selected sample of 256 Higher National Diploma II students of the Federal Polytechnic, Idah, Nigeria, who were exposed to EE. To analyse the data collected, partial least squares structural equation modelling (PLS-SEM) was performed using SmartPLS 2.0.M3 software. Findings: Data analysis showed a significantly positive relationship between EE and students' EIs on the one hand and between EE and perceived entrepreneurial lecturers (PELs) on the other hand. It was also found that PELs had a significantly positive link with students' EIs. Further analysis indicated that PELs had a mediating effect on the relationship between EE and students' EIs. Research limitations/implications: This study was a single institutional study. Thus, the generalisability of its findings to other institutions is limited. Extending the research to other institutions and countries might be required to validate the findings presented. Practical implications: This research work has some insightful implications for the teaching of EE. By implication, it provides an answer to the question: who should teach EE? To achieve greater impact of EE on students' EIs and behaviours, entrepreneurial lecturers are required. It implies that EE lecturers should be entrepreneurially inclined. They should demonstrate sufficient entrepreneurial attitudes, intentions and behaviours. Social implications: It has been argued that graduate unemployment constitutes a social problem to the society. In this regard, the suggestions made in this paper, if applied, would help resolve the problem of graduate unemployment in Nigeria and other countries. Originality/value: This study is the first to provide empirical evidence of the role of entrepreneurial lecturers in the relationship between EE and students' EIs. It has demonstrated that entrepreneurial lecturers could transfer the influence of EE to students' EIs. Also, it has confirmed that EE lecturers are critical in the EE-students' EIs relationship. Overall, this study makes a significant contribution to the discussion on how to enhance the effectiveness of EE in influencing students' EIs and behaviours.